Knowledge Attitude and Practice Regarding Antenatal Care among Pregnant Women in Rural Area of Lahore - Akhtar, Shahnaz; Hussain, Muhammad; Majeed, Iram; Afzal, Muhammad (International Journal of Social Sciences and Management, 2018)
Background: Prenatal care is medical valuation of mother and fetus, for the duration of gestation used for getting best possible result for the mother and child. Early observation and ongoing care during pregnancy provided more favorable births compared to no prenatal observation. Methodology: The quantitative cross-sectional study design was used with convenient sampling (n=133) from community of Hussain Abad Lahore. Pregnant women between the ages of 20 to 45 years of age. Data was analyzed on SPSS 21 version and application of chi-square test (p=<0.05). Result: The respondents 69.1% (n=94) were identified that pregnant women require to go for their checkup. This study reveals that (n=31) 21.4% participants were agree, (n=98)71.1% participants were disagreed, (n=06)4.4% were neutral that they have Seek antenatal care regularly during pregnancy. 83.1% women believe that antenatal checkup is worthy to monitor mother & fetus’ well-being. Conclusion: 64.7% pregnant women response in yes regarding knowledge about antenatal care. The attitude was shown positive somewhere as 69.6% women were agree and as well as negative, also as 30.1% respondents were disagreed and therefore 61% participants have positive practices towards antenatal care. There was significant association between qualification and knowledge of expectant women about prenatal care, significant association in qualification and attitude and there was insignificant association in qualification and practices. Int. J. Soc. Sc. Manage. Vol. 5, Issue-3: 155-162